Facile isomerization of silyl enol ethers catalyzed by triflic imide and its application to one-pot isomerization–(2 + 2) cycloaddition - Inanaga, Kazato; Ogawa, Yu; Nagamoto, Yuuki; Daigaku, Akihiro; Tokuyama, Hidetoshi; Takemoto, Yoshiji; Takasu, Kiyosei (Beilstein Journal of Organic Chemistry, 2012)
A triflic imide (Tf2NH) catalyzed isomerization of kinetically favourable silyl enol ethers into thermodynamically stable ones was developed. We also demonstrated a one-pot catalytic reaction consisting of (2 + 2) cycloaddition and isomerization. In the reaction sequence, Tf2NH catalyzes both of the reactions.
Keywords: isomerization; one-pot reaction; organocatalysis; silyl enol ethers; triflic imide

(untitled) - Brownbridge, P. (Synthesis, 1983)

(untitled) - Brownbridge, P. (Synthesis, 1983)

(untitled) - Poirier, J.-M. (Org. Prep. Proced. Int., 1988)

(untitled) - Stork, G.; Hudrlik, P. F. (J. Am. Chem. Soc., 1968)

(untitled) - Deyine, A.; Dujardin, G.; Mammeri, M.; Poirier, J.-M. (Synth. Commun., 1998)

(untitled) - Ishihara, K.; Nakamura, H.; Nakamura, S.; Yamamoto, H. (J. Org. Chem., 1998)

(untitled) - Aikawa, H.; Kaneko, T.; Asao, N.; Yamamoto, Y. (Beilstein J. Org. Chem., 2011)

(untitled) - Takasu, K. (Synlett, 2009)

(untitled) - Ishihara, K.; Hiraiwa, Y.; Yamamoto, H. (Synlett, 2001)

(untitled) - Inanaga, K.; Takasu, K.; Ihara, M. (J. Am. Chem. Soc., 2005)

(untitled) - Boxer, M. B.; Yamamoto, H. (J. Am. Chem. Soc., 2006)

(untitled) - Takasu, K.; Miyakawa, Y.; Ihara, M.; Tokuyama, H. (Chem. Pharm. Bull., 2008)

(untitled) - Kurahashi, K.; Takemoto, Y.; Takasu, K. (ChemSusChem, 2012)

(untitled) - Fogg, D. E.; dos Santos, E. N. (Coord. Chem. Rev., 2004)

(untitled) - Shindoh, N.; Takemoto, Y.; Takasu, K. (Chem.–Eur. J., 2009)

(untitled) - Shindoh, N.; Tokuyama, H.; Takemoto, Y.; Takasu, K. (J. Org. Chem., 2008)

(untitled) - Takasu, K.; Tanaka, T.; Azuma, T.; Takemoto, Y. (Chem. Commun., 2010)

(untitled) - Azuma, T.; Takemoto, Y.; Takasu, K. (Chem. Pharm. Bull., 2011)